Synthesis and characterization of meloxicam eutectics with mandelic acid and saccharin for enhanced solubility - Fernandes, Richard Perosa [UNESP]; de Carvalho, Ana Carina Sobral [UNESP]; Ekawa, Bruno [UNESP]; do Nascimento, Andre Luiz Soares Carneiro [UNESP]; Pironi, Andressa Maria [UNESP]; Chorilli, Marlus [UNESP]; Caires, Flávio Junior [UNESP] (Taylor & Francis, 2020)
Meloxicam (MLX) is a non-steroidal anti-inflammatory which is practically insoluble in water, requiring high concentrations to reach therapeutic levels and causing frequently gastrointestinal effects. In this way, the aim of this study was to synthesize two eutectic mixtures of MLX with mandelic acid (MND) and saccharin (SAC) by liquid-assisted grinding resulting in a multicomponent material with enhanced solubility. Mixtures were studied in different stoichiometric and eutectic point was found for each eutectic by Binary phase diagram and Tamman’s triangle, with 0.33 molar fraction of MLX for SAC and MND. Eutectics were characterized by thermoanalytical techniques (TG-DSC, EGA, DSC, and DSC microscopy), infrared spectroscopy, and X-ray powder diffraction. Thermal behavior was studied and videos of the materials being heated were available. A polymorphic transition was discovered and studied for MLX-MND eutectic. Each new system was evaluated by solubility, dissolution, and hygroscopicity tests. Eutectics showed an increase in solubility of 1.7× (MLX-MND1), 3.1× (MLX-MND2), and 1.3× (MLX-SAC) with slower dissolution profile when compared with MLX. All new solid forms showed high hygroscopicity at 98% relative humidity with 27.9 and 58.9% increase in mass at day four for MLX-SAC and MLX-MND, deliquescence occurs at day 6. The experiments and analysis in this study help to understand the behavior of eutectics and evaluate them as an approach to modify properties in drugs.
Keywords: dissolution; eutectic; hygroscopicity; Meloxicam; solubility